The Effect Of Environment, Social, Governance (ESG Disclosure) And Profitabiltiy On Firm Value With Audit Fee As Moderating Variable : Study Of Energy Sector Companies Listed On The Indonesian Stock Exchange Period 2019 - 2022 - Ridwansyah Ridwansyah; Herlin Tundjung Setijaningsih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to analyze the influence of Environmental, Social, Governance Disclosure (ESG Disclosure) and Profitability on the Value of Energy Sector Companies Listed on the Indonesian Stock Exchange with Fee audit as a Moderating Variable. The population of this research is energy sector companies listed on the Indonesia Stock Exchange for the 2019-2022 period. The method used is quantitative, panel data regression model using the help of the eviews application, the number of samples obtained is 108 with a sampling technique using the purposive sampling method. The findings show that profitability has a positive effect on firm value. Environmental disclosure has a negative effect on firm value. Social and governance disclosures have no effect on firm value. Fee audit weakens the influence of profitability on firm value. Fee audit is unable to moderate the influence of the environment, social and governance on firm value